2020
DOI: 10.3390/nu12010156
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Age at Diagnosis and Nutritional Course of Celiac Disease in the Last Two Decades

Abstract: The frequency of celiac disease (CD) has increased along time, with relevant changes reported in geographical variations, clinical presentation and nutritional repercussions. In recent years, some celiac patients are presenting overweight/obesity, but it is unclear how frequent this is and to what extent undernutrition remains a concern. This is relevant because CD tends to be overlooked in overweight patients. With this in mind, we assessed age at diagnosis, clinical characteristics and nutritional status of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Most studies in the literature have shown that CD patients (at diagnosis) have a lower BMI than the general population [10][11][12]; therefore, weight gain from a GFD may have positive effects on these patients. However, it has been clearly demonstrated that nowadays, an increasing number of CD patients present with a normal or high BMI at the time of diagnosis [3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies in the literature have shown that CD patients (at diagnosis) have a lower BMI than the general population [10][11][12]; therefore, weight gain from a GFD may have positive effects on these patients. However, it has been clearly demonstrated that nowadays, an increasing number of CD patients present with a normal or high BMI at the time of diagnosis [3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, at the time of diagnosis, patents with CD had a reduced body mass index (BMI) compared to the general population [3]. In the last few decades, increasing numbers of CD patients with a normal or high BMI at the time of diagnosis was reported [4][5][6][7][8][9]. This could be due to the fact that early diagnosis has become more frequent in recent years (late diagnoses were more common in the past), allowing for a reduction in the rate of both intestinal mucosal atrophy and related malabsorption [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the nutritional status of the general population is of utmost importance for the correct interpretation of BMI in children at the time of the diagnosis of CD. It is vital to bear in mind that celiac disease can develop in overweight/obese patients, reflecting the individual predispositions (i.e., genetic, nutritional and environmental factors) [ 66 , 67 ]. Furthermore, the worldwide prevalence of overweight and obesity in children has increased over the past two decades; in fact, it is estimated that 60 million children will have been overweight or obese by 2020 [ 68 ].…”
Section: Gfd and Its Risksmentioning
confidence: 99%
“…Formerly, classical CD with malnutrition due to intestinal malabsorption was the most prevalent [ 5 ]. Recently, the proportion of non-classical and asymptomatic CD patients with normal or high body weight (BW) already at the time of the diagnosis has been increasing rapidly, which can be attributed, among other things, to increasing disease awareness and accurate and accessible serological testing [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%